Antimicrobial activity of bacterial nanocellulose modified with chestnut extract - Melro, Liliana Sofia Silva Ferreira Pinto (2022)
Chestnut wood extracts are rich in tannins that exhibit numerous health-promoting properties. The incorporation of 5% (w/v) chestnut extract within the nanofibrous structure of bacterial nanocellulose (BNC) produced by Gluconacetobacter hansenii ATCC 53582 was obtained through exhaustion. This simple processing methodology resulted in a flexible (upon addition of 2% (w/v) glycerol), biodegradable, biocompatible nanocomposite for potential application in medical appliances.